2013 35th International Conference on Software Engineering (ICSE) 2013
DOI: 10.1109/icse.2013.6606673
|View full text |Cite
|
Sign up to set email alerts
|

Temporal code completion and navigation

Abstract: Abstract-Modern IDEs make many software engineering tasks easier by automating functionality such as code completion and navigation. However, this functionality operates on one version of the code at a time. We envision a new approach that makes code completion and navigation aware of code evolution and enables them to operate on multiple versions at a time, without having to manually switch across these versions. We illustrate our approach on several example scenarios. We also describe a prototype Eclipse plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…API code completion tools [1,5,9] improve existing IDE's code completion features by integrating information mined from version control systems. Robbes et al [9] rank most recently used API methods higher than other APIs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…API code completion tools [1,5,9] improve existing IDE's code completion features by integrating information mined from version control systems. Robbes et al [9] rank most recently used API methods higher than other APIs.…”
Section: Related Workmentioning
confidence: 99%
“…Existing code completion engines either provide simple "quick fix" for API method calls and object instantiation values, or perform complex edit operations based on predefined templates. Several code completion approaches [1,5,9] rank certain method targets higher than others based on the patterns found in the codebase or version histories. Omar et al [8] suggest possible values to use based on a predefined value set.…”
Section: Introductionmentioning
confidence: 99%
“…On similar lines, Lee et al [14] have an additional temporal dimension for evolutionary information on the code. In a collaborative work environment, they propose that such information could make development tasks easier.…”
Section: Related Workmentioning
confidence: 99%
“…Lee et al [9] first introduced the idea about adding temporal dimension in code completion. The proposed idea was that code changes can be shown through code completion.…”
Section: Related Workmentioning
confidence: 99%
“…There are several research works found in literature which focused on establishing connection between software artifacts [3], [8], [9], [10]. These aimed to assist software engineer during development and maintenance phase.…”
Section: Introductionmentioning
confidence: 99%